A report on the practice-in-industry training in fish processing technology. - Banda, Maria Carolina M. (Diliman, Quezon City College of Fisheries, University of the Philippines, 1978)
Fresh samples of roundscad (Decapterus macrosoma) were obtained and salted by two methods such as Kench-salting and brine salting. Kench-salting was done by individually salting the samples, arranging in racks where they were kept in contact with salt throughout the storage period. Brine salting, on the other hand, was done by soaking the samples in brine solution for varying lengths of time, namely for 1 hour, 4 hours, and until equilibrium was reached. This is to effect salt content differences in the brine-salted samples. After soaking in brine, the samples were dried, packed in plastic bags, and stored at room temperature (27~'C.). Peroxide value determination and subjective evaluation of flavour and odor of the different samples were done periodically in order to follow up the development of rancidity during storage at 27~'C. As supplementary tests, the moisture and salt contents were also determined. Results have shown that the rate at which fat autoxidation proceeded varied for the different dried, salted fish samples. The Kench-salted fish showed the fastest rate. Of the brine-salted samples, the one soaked in brine solution until equilibrium was reached showed the fastest rate of autoxidation, followed by that salted for 4 hours, and slowest for that sample salted for one hour, the rate being increasing with increasing salt content. It was also found that for this particular dried, salted fish, the development of rancid favour and odor was relatively slow. No readily detectable and objectionable rancid flavour and odor was detected until the end of the storage period. It was shown further that correlation between flavour and odor scores and peroxide values was insignificant.
Thesis (Undergraduate. Bachelor of Science in Fisheries major in Fish Processing Technology) College of Fisheries, University of the Philippines, c1978.
Keywords: Fishery processing